2013
DOI: 10.1186/2051-4190-23-13
|View full text |Cite
|
Sign up to set email alerts
|

FISH and tips: a large scale analysis of automated versus manual scoring for sperm aneuploidy detection

Abstract: BackgroundApproximately 1% of the spermatozoa found in ejaculate of healthy men are aneuploid and this rate increases in the population of subfertile and infertile men. Moreover, fertilization with these aneuploid sperm can lead to impaired embryo development. Fluorescent In Situ Hybridization (FISH) is the common cytogenetic tool used for aneuploidy screening on sperm. However, it is a time-consuming technique and cytogenetic or in vitro fertilization laboratories cannot routinely use it and face the increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…To date, we and others largely agree that automated systems can reliably assess sperm aneuploidy (Netten et al 1997, Baumgartner et al 2001, Perry et al 2007, 2011, Carrell & Emery 2008, Molina et al 2009, Tempest et al 2010, Martinez et al 2013, Branch et al 2017. Some studies have reported substantial reductions in analysis time (Branch et al 2017), but it is important to consider some challenges.…”
Section: The Advantages and Disadvantages Of Fish To Assess Sperm Anementioning
confidence: 99%
See 1 more Smart Citation
“…To date, we and others largely agree that automated systems can reliably assess sperm aneuploidy (Netten et al 1997, Baumgartner et al 2001, Perry et al 2007, 2011, Carrell & Emery 2008, Molina et al 2009, Tempest et al 2010, Martinez et al 2013, Branch et al 2017. Some studies have reported substantial reductions in analysis time (Branch et al 2017), but it is important to consider some challenges.…”
Section: The Advantages and Disadvantages Of Fish To Assess Sperm Anementioning
confidence: 99%
“…Due to the relatively low levels of sperm aneuploidy, thousands of sperm are required to be scored, which is labor intensive. This issue is readily solvable with the advent of various automated systems that have the capability to accurately and reliably assess sperm aneuploidy (Netten et al 1997, Baumgartner et al 2001, Perry et al 2007, 2011, Carrell & Emery 2008, Molina et al 2009, Tempest et al 2010, Martinez et al 2013, Branch et al 2017. In reality, we are unable to test the individual sperm that will be used in ART; thus, it can only provide a generalized overview of the levels of aneuploidy in a semen sample.…”
Section: Why Is Sperm Aneuploidy Screening Rarely Considered In Art?mentioning
confidence: 99%
“…1 and 2 ), aneuploidy can be evaluated on the same slide, at a single cell level of resolution, together with other techniques and biomarkers such as IHC and Ki-67 for an optimal evidence based evaluation of malignancy, clonality, tissue of origin and replication rate of the lesion [ 129 – 131 ]. Progress in semiautomatic sperm scoring has advanced precision in determining sperm aneuploidy rates while saving on time and operator burden [ 132 , 133 ] and is making human biomarker assessment more feasible for both cancer biology and molecular epidemiology laboratories [ 134 ].
Fig.
…”
Section: Techniques Available To Assess Aneuploidy In Precancerous Anmentioning
confidence: 99%
“…To our knowledge, eight previous studies have compared manual counting of FISH hybridized sperm to automated spot counting (15)(16)(17)(18)(19)(20)(21)(22). To our knowledge, eight previous studies have compared manual counting of FISH hybridized sperm to automated spot counting (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Designing reliable methods capable of accurately determining aneuploidy is important for advancing aneuploidy detection, etiologic research, and ultimately clinical application. To our knowledge, eight previous studies have compared manual counting of FISH hybridized sperm to automated spot counting (15)(16)(17)(18)(19)(20)(21)(22). These studies used wide-field epifluorescence microscopy to validate counting software such as MetaSystems or Spot AX.…”
Section: Introductionmentioning
confidence: 99%